PENGEMBANGAN MODEL PEMBELAJARAN GUIDED PROJECT BASED LEARNING UNTUK MAHASISWA SLOWLEARNER - Rahmat Kurniawan (Universitas Muria Kudus, 2020)
This research and development aims to developing a learning model Guided Project Based Learning that can be implemented for slow learners or slow learners or normal students in one learning environment. This model was applied in Multimedia II course in STIKI Malang visual communication design study program for five meetings.The development method for developing this Guided Project Based Learning learning model uses the ADDIE model developed by Dick and Carey. The steps of developing a learning model using the ADDIE development model consist of 5 steps, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The sample in this study was the 5th semester visual communication design student where there were slowlearner students. Data was collected by mapping through the stages of psychological testing.The results of the mapping found 1 student with special needs slow learner type. Implementation of the GPBL model proves students can understand the material and follow systematically the design of simple games. In addition, the student is actively able to explain game design concepts.